Research on the impact of User-Generated Content (UGC) in shaping the purchase behavior of environmentally friendly products and the moderatings role of brand reputation - Tu Ngoc Tran; Nguyen Phan Thu Hang (PLoS ONE, 2025)
This paper aims to explore the effect of User-Generated Content (UGC) on the purchasing behavior of environmentally friendly products at Hospitality and Food Service Industry in Vietnam, particularly in Ho Chi Minh City. A conceptual model has been developed based on literature reviews and empirical studies. Furthermore, the Partial Least Squares Structural Equation Modeling (PLS-SEM) method was employed to investigate the impact of UGC on the purchasing behavior of environmentally friendly products at Hospitality and Food Service Industry in Vietnam. The results confirm that environmental concerns, attitudes, and the intention to purchase green products are all positively and significantly influenced by UGC. Especially, the results validate that brand reputation plays a moderating role in the connections between UGC and environmental concern, UGC and environmental attitude, as well as the relationship between the intention to purchase environmentally friendly products and actual purchasing behavior.